The mediating role of anxiety in the relationship between misophonia and quality of life: findings from the validated Turkish version of MisoQuest - Ay, Ezgi; Huviyetli, Mert; Çakmak, Eda (Frontiers in Psychology, 2024)
Introduction Misophonia is a disorder characterized by decreased tolerance to certain sounds or their associated stimuli, and many measurement tools have been developed for its diagnosis and evaluation. The aims of the current study were to develop the Turkish version of MisoQuest, a fully validated misophonia questionnaire, to evaluate the relationships between misophonia, anxiety, and quality of life, and to examine the mediating role of anxiety in the relationship between misophonia and quality of life. Methods The reliability of the Turkish version of MisoQuest was conducted using data from 548 participants (Mean age = 28.06 ± 9.36). Then, the relationships between misophonia, anxiety, and quality of life were evaluated in a separate sample of 117 participants (Mean age = 25.50 ± 6.31) using the State–Trait Anxiety Inventory (STAI) and the Short Form 36 (SF-36) questionnaire. Results The results showed that the Turkish version of MisoQuest has good psychometric properties. Close-to-moderate positive correlations were found between misophonia and anxiety, and weak negative correlations were found between misophonia and quality of life. Anxiety mediated the relationships between misophonia and quality of life. Discussion These results emphasize that misophonia may be an important problem affecting people’s quality of life and reveal the mediating role of anxiety on this effect.